Critical review of the evidence for Vojta Therapy: a systematic review and meta-analysis - Sánchez-González, Juan Luis; Sanz-Esteban, Ismael; Menéndez-Pardiñas, Mónica; Navarro-López, Víctor; Sanz-Mengíbar, José Manuel (Frontiers in Neurology, 2024)
Introduction: Linking the theoretical framework of neurophysiotherapy approaches with detailed analysis of central motor control mechanisms influencing motor behavior is essential. Vojta therapy (VT), often wrongly seen as exclusively pediatric, affects various functional disorders by modulating central patterns. This study aims to review evidence on VT effectiveness across conditions in both adult and pediatric populations, analyzing therapeutic mechanisms, particularly motor control modulation. Aim: This systematic review aims to delineate evidence on VT efficacy across conditions and understand common therapeutic mechanisms, particularly neuromodulation of motor control parameters. Methods: PubMed, Cochrane Library, SCOPUS, Web of Science, and Embase were searched for eligible studies. Methodological quality was assessed using PEDro list and Risk-Of-Bias Tool for randomized trials. Random-effects meta-analyses with 95% CI were used to quantify change scores between VT and control groups. Certainty of findings was evaluated using GRADE. Results: Fifty-five studies were included in qualitative analysis, and eighteen in meta-analysis. Significant differences in cortical activity (p=0.0001) and muscle activity (p=0.001) were observed in adults undergoing VT compared to control, as well as in balance in those with multiple sclerosis (p<0.03). Non-significant differences were found in gross motor function, oxygen saturation, respiratory rate, height, and head circumference in pediatrics. Conclusion: While current evidence supporting VT is limited in quality, indications suggest its potential usefulness for treating respiratory, neurological, and orthopedic pathologies. This systematic review and meta-analysis highlight VT's robust neurophysiological mechanisms, potentially effective for treating balance in adult neurological pathology, confirming neuromodulation of motor control areas.